Uji Aktivitas Anti-Inflamasi Ekstrak Kulit Terong Ungu (Solanum melongena L.) Terhadap Tikus Putih Galur Wistar (Rattus norvegicus) Yang Diinduksi Karagenan - Heryanto, Jessica Diva; Dewi, Ni Wayan Sucindra; Ernawati, Desak Ketut (E-Jurnal Medika Udayana; Vol 13 No 4 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i04.P03, 2024)
Inflammation is the human body’s defense to prevent tissue damage due to different kinds of factors. The purple eggplant peel ( Solanum melongena L .) may have the potential to have anti-inflammatory properties due to containing nasunin, which is a phenolic, flavonoid anthocyanin substance by inhibiting cyclooxygenase pathway. This research was done to prove the anti-inflammatory effect of purple eggplant peel extract in rats. The research method was conducted by true experimental post-test only control-group design. 25 rats were divided into 5 groups with different treatments which are: positive control, negative control, purple eggplant peel extract with a dose of 0,3 mg/gBW, 6 mg/gBW and 0,9 mg/gBW. The data measured was the decrease of edema volume induced by carrageenan at hours-0 1, 2, 3, 4, 5, and 6. Data analysis was performed at the 4 th hour using ANOVA and post-hoc LSD tests. The results of the study found that there were significant differences between the negative control group and the positive control group and the entire treatment group. The conclusion of this study was that purple eggplant peel extract had anti-inflammatory activity with the best effectiveness at a dose of 0,9 mg/gBW .